Book Reviews (The ecumenical review, 1962)
Book reviewed in this article: CHRISTIAN DIVISIONS IN HISTORICAL LIGHT: How we Got our Denominations, by Stanley I. Stuber CHRISTIAN DIVISIONS IN HISTORICAL LIGHT: The English Religious Tradition, by Norman Sykes CHRISTIAN DIVISIONS IN HISTORICAL LIGHT: The Protestant Mind of the English Reformation 1570–1640 by Charles H. George and Katherine George Worship and Theology in England — From Watts and Wesley to Maurice 1690–1850 by Horton Davies THE CHALLENGE OF A TIMELY STUDY: The Churches and Rapid Social Change, by Paul Abrecht Man in rapid Social Change, by Egbert de Vries SERVICE BY THE CONGREGATION: Diakonie der Gemeinde, Arbeitsbuch für die Nächstenhilfe, edited by Hans Christoph von Hase THE RECOVERY OF CONFIDENCE IN THE BIBLE: The Meaning of Sacred Scriptures, by Louis Bouyer THE RECOVERY OF CONFIDENCE IN THE BIBLE: The English Bible, by F. F. Bruce THE RECOVERY OF CONFIDENCE IN THE BIBLE: The New English Bible THE RECOVERY OF CONFIDENCE IN THE BIBLE: The New English Bible THE RECOVERY OF CONFIDENCE IN THE BIBLE: The Bible in the Age of Science, by Alan Richardson THE RECOVERY OF CONFIDENCE IN THE BIBLE: Take and Read, by E. H. Robertson THE RECOVERY OF CONFIDENCE IN THE BIBLE: The Bible in our Time, by E.H. Robertson TESTAMENT OF A YWCA LEADER: Women and the New East by Ruth Frances Woodsmall, with a foreword by Bayard Dodge THE CATHOLICS AND SOCIAL LIFE: Les catholiques et la politique, by A. Delmasure THE CATHOLICS AND SOCIAL LIFE: Wirtschaft und Gesellschaft Heute DUTCH CONTRIBUTIONS TO ECUMENICAL THINKING: Oecumene in het Vizier. Fesstbundel voor Dr. W. A. Visser't Hooft DUTCH CONTRIBUTIONS TO ECUMENICAL THINKING: De Kerk en de Pinkstergroepen DUTCH CONTRIBUTIONS TO ECUMENICAL THINKING: De Oecumene, by Dr. W. H. van de Pol DUTCH CONTRIBUTIONS TO ECUMENICAL THINKING: He Concilie in de Beleving van het Geloof, by Prof ECUMENICAL HIGHWAYS (II): The Nature and Calling of the Church, by William Stewart ECUMENICAL HIGHWAYS (II): Church and Sacraments in Divided Christendom, by Leonard Hodgson ECUMENICAL HIGHWAYS (II): Unity, Hope and experience, by Michael Hollis ECUMENICAL HIGHWAYS (II): We were Brought Together edited by David H. Taylor ECUMENICAL HIGHWAYS (II): Met al de Heiligen